Prolonged Cardiac Monitoring and Stroke Recurrence: A Meta-analysis. (10th May 2022) - Tsivgoulis, Georgios; Triantafyllou, Sokratis; Palaiodimou, Lina; Grory, Brian Mac; Deftereos, Spyridon; Köhrmann, Martin; Dilaveris, Polychronis; Ricci, Brittany; Tsioufis, Konstantinos; Cutting, Shawna; Magiorkinis, Gkikas; Krogias, Christos; et al.
Abstract : Background and Objectives: Prolonged poststroke cardiac rhythm monitoring (PCM) reveals a substantial proportion of patients with ischemic stroke (IS) with atrial fibrillation (AF) not detected by conventional rhythm monitoring strategies. We evaluated the association between PCM and the institution of stroke preventive strategies and stroke recurrence. Methods: We searched MEDLINE and SCOPUS databases to identify studies reporting stroke recurrence rates in patients with history of recent IS or TIA receiving PCM compared with patients receiving conventional cardiac rhythm monitoring. Pairwise meta-analyses were performed under the random effects model. To explore for differences between the monitoring strategies, we combined direct and indirect evidence for any given pair of monitoring devices assessed within a randomized controlled trial (RCT). Results: We included 8 studies (5 RCTs, 3 observational; 2, 994 patients). Patients receiving PCM after their index event had a higher rate of AF detection and anticoagulant initiation in RCTs (risk ratio [RR] 3.91, 95% CI 2.54–6.03; RR 2.16, 95% CI 1.66–2.80, respectively) and observational studies (RR 2.06, 95% CI 1.57–2.70; RR 2.01, 95% CI 1.43–2.83, respectively). PCM was associated with a lower risk of recurrent stroke during follow-up in observational studies (RR 0.29, 95% CI 0.15–0.59), but not in RCTs (RR 0.72, 95% CI 0.49–1.07). In indirect analyses of RCTs, the likelihood of AF detection and anticoagulation initiation was higher for implantable loop recorders compared with Holter monitors and external loop recorders. Discussion: PCM after an IS or TIA can lead to higher rates of AF detection and anticoagulant initiation. There is no solid RCT evidence supporting that PCM may be associated with lower stroke recurrence risk.